Influence of the metabolic profile of a swimmer on the energetic contributions and possible training stimulus during interval training - an in silico analysis. - Weber, S.; Tran, C.; Mader, A. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION Work to rest ratio in interval training (IT) has been a focus of scientific research in order to understand how different interval training patterns effect energy metabolism and therefore the possible training stimulus2. For example the time spent at >90% of VO2max has shown correlate with improvements of VO2max (X). To our knowledge, little to no information exists how the physiological make up of an athlete effects energetic contribution and possible training stimulus during IT.